ANALYSIS OF THE POTENTIAL OF THE HEXA HELIX MODEL IN THE PREVENTION AND HANDLING OF DOMESTIC VIOLENCE IN THE SPECIAL REGION OF YOGYAKARTA - Nur Rizka Riyana; Muhammad Fajrus Shodiq (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2026)
Domestic Violence (KDRT) in Indonesia still faces various problems and challenges. In the Special Region of Yogyakarta, KDRT itself continues to experience dynamics. This study aims to understand how the potential of the hexa helix model can be used to prevent and manage KDRT in the Special Region of Yogyakarta, given that victims from 2022 to 2025 continue to experience fluctuations, requiring special attention to foster harmonious household relationships in the future. This study uses theories regarding the elements of the hexa helix model. The novelty of this research is the cross-sector involvement in the elements of the hexa helix model, namely academics, the business world, community, government, law and regulation, as well as media, to analyze its potential in the prevention and handling of KDRT in Yogyakarta. This study uses qualitative research methods, including observation, interviews, and documentation. The results of this study indicate that the potential of the hexa helix model for preventing and handling domestic violence in the Special Region of Yogyakarta is quite promising. However, several factors affect the implementation of the hexa helix model, so recommendations such as unifying the vision, strengthening collaboration, and conducting regular monitoring and evaluation are needed.